The Phenomenon of Language Policy: Theoretical Aspects - Н.A., Оспaн (Journal of Oriental Studies, 2019)
This article discusses the phenomena of language policy and its theoretical aspects. The language planning defines the direct connection between the issues of development of interethnic and international relations, strengthening of friendship and mutual respect and interethnic harmony at the international level, political stability in the state. The study of these aspects is relevant today. This article reveals the concept of language policy, widely used in science. In the main part we wanted to show several definitions obtained from the reference dictionary of political science, methodological terms and concepts, linguistic and sociolinguistic dictionaries, general linguistics. Language policy is a system of measures and legislation implemented by the administrative authorities or public institutions of the country, has specific socio-linguistic goals. Thus, a number of definitions of the concept of language policy are presented and the complexity is mentioned. In this article we want to list several definitions obtained from the reference dictionary of political science, methodological terms and concepts, linguistic and sociolinguistic dictionaries, General linguistics. Language policy – a system of measures and legislation implemented by the administrative authorities or public institutions of the country, has specific socio-linguistic goals. Key words: language policy, language planning, language problems, political stability, state language, theoretical aspects.